2012
DOI: 10.1016/j.jaut.2011.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Defective cell death signalling along the Bcl-2 regulated apoptosis pathway compromises Treg cell development and limits their functionality in mice

Abstract: The Bcl-2 regulated apoptosis pathway is critical for the elimination of autoreactive lymphocytes, thereby precluding autoimmunity. T cells escaping this process can be kept in check by regulatory T (Treg) cells expressing the transcription and lineage commitment factor Foxp3. Despite the well-established role of Bcl-2 family proteins in shaping the immune system and their frequent deregulation in autoimmune pathologies, it is poorly understood how these proteins affect Treg cell development and function. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 49 publications
1
27
2
Order By: Relevance
“…On the other hand, recent studies have shown that Foxp3 + expression protects T reg cells from activation-induced cell death (46). A differential expression of the BimYBcl-2 axis in T reg cells and T con cells was suspected to contribute to apoptosis resistance of T reg cells (47,48) but was not found to be the case in our study (data not shown). A most recent study suggests that Mcl-1, but not Bcl-x L or Bcl-2, is essential for T reg cell survival (49).…”
Section: Discussioncontrasting
confidence: 76%
“…On the other hand, recent studies have shown that Foxp3 + expression protects T reg cells from activation-induced cell death (46). A differential expression of the BimYBcl-2 axis in T reg cells and T con cells was suspected to contribute to apoptosis resistance of T reg cells (47,48) but was not found to be the case in our study (data not shown). A most recent study suggests that Mcl-1, but not Bcl-x L or Bcl-2, is essential for T reg cell survival (49).…”
Section: Discussioncontrasting
confidence: 76%
“…It has been reported that A1 mRNA levels are high in splenic Tregs but even higher in thymic Tregs when compared with the expression observed in CD4 + Tcons. 34 However, this was not demonstrated at the protein level in this study. Our results nonetheless support similar or even lower protein expression levels of A1 in Tregs compared with Tcons.…”
contrasting
confidence: 68%
“…Interestingly, extrathymic Treg-cell production was shown to be of importance to control inflammatory Th2 responses at environmental interfaces and commensal microbiota composition [26]. The age-related defect in Foxp3 induction identified here can explain why Treg cells fail to control dysregulated inflammation found at mucosal sites in elderly [10,27] despite a global accumulation of Treg cells, due to their increased resistance to apoptosis [28]. Our findings indicate that impairment of extrathymic induction of Foxp3 with age is an important feature, which may compromise the success of tolerance induction protocols in elderly.…”
Section: Discussionmentioning
confidence: 79%